2015
DOI: 10.1539/joh.14-0218-oa
|View full text |Cite
|
Sign up to set email alerts
|

Risk and preventive factors for heat illness in radiation decontamination workers after the Fukushima Daiichi Nuclear Power Plant accident

Abstract: Risk and preventive factors for heat illness in radiation decontamination workers after the Fukushima Daiichi Nuclear Power Plant accident: Takeyasu Kakamu, et al. Department of Hygiene and Preventive Medicine, Fukushima Medical University School of Medicine Objective The aim of this study was to reveal factors related to heat illness in radiation decontamination workers and determine effective preventive measures. Methods A self‐administered questionnaire was sent to 1,505 radiation decontamination workers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Previous studies, including ours 2) , have shown that exertional heat illness mainly occurs in young workers. Although younger age tends to be associated with better physiological heat tolerance than older age 10 , 11) , age has been identified as a risk factor 12) .…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…Previous studies, including ours 2) , have shown that exertional heat illness mainly occurs in young workers. Although younger age tends to be associated with better physiological heat tolerance than older age 10 , 11) , age has been identified as a risk factor 12) .…”
Section: Introductionmentioning
confidence: 50%
“…Previously, we reported that more than half of the decontamination workers experienced symptoms of heat illness during one summer 2) . This was despite the government demanding that employers protect their workers from risks such as heat illness 3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' data were obtained from our previous study designed to investigate associations of behavioral, social, mental, and environmental factors with occupational health among radiation decontamination workers in Fukushima Prefecture, Japan 10) . We asked all 213 companies, who were involved in radiation decontamination in Fukushima Prefecture and attended a training program against radiation exposure held by the Fukushima Occupational Health Promotion Center from April to July 2013, to select approximately 10 workers to complete the questionnaires for the present study.…”
Section: Study Participantsmentioning
confidence: 99%
“…However, the support for mental health especially, perceived anxiety over radiation exposure among decontamination workers is insufficient compared with the support for physical health. As Kakamu et al reported, many more workers are engaged in the decontamination work in places with relatively lower dose rates than there are in places with higher dose rates; therefore, the risk of physical health problems from radiation exposure is low 10) . Moreover, prior to starting their work, the workers are educated on safety management and decontamination methods, using a text made by the Japanese government 11) .…”
Section: Introductionmentioning
confidence: 99%